2011
DOI: 10.1016/j.biocontrol.2011.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative food webs of herbivore and related beneficial community in non-crop and crop habitats

Abstract: a b s t r a c tQuantitative food webs were constructed from the data collected, using visual observation technique, from May to July in 2005 and 2006 to describe separately the trophic relationships between the community of aphids and their natural enemies of predators and parasitoids in agricultural and semi-natural habitats in Gembloux, Belgium. In the web, a total of six aphid attacked by six parasitoid and 21 predator species were recorded in this study; 50 and 33 links between aphid and natural enemy spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…Cultivated habitats are abundant but temporary resources for phytophagous insects and their associated natural enemies, while uncultivated habitats can act as refuges for these organisms because they are more stable environments. These habitats provide alternative prey for predators or hosts for parasitoids (Alhmedi et al, 2011;Rusch et al, 2012). Many studies have demonstrated the importance of semi-natural habitats and their alternative resources in agroecosystems in determining the abundance and diversity of pest natural enemies (Tscharntke et al, 2007;Ricci et al, 2009Ricci et al, , 2011 and their efficiency for biological control (Langer & Hance, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Cultivated habitats are abundant but temporary resources for phytophagous insects and their associated natural enemies, while uncultivated habitats can act as refuges for these organisms because they are more stable environments. These habitats provide alternative prey for predators or hosts for parasitoids (Alhmedi et al, 2011;Rusch et al, 2012). Many studies have demonstrated the importance of semi-natural habitats and their alternative resources in agroecosystems in determining the abundance and diversity of pest natural enemies (Tscharntke et al, 2007;Ricci et al, 2009Ricci et al, , 2011 and their efficiency for biological control (Langer & Hance, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, few studies predicting a potential for apparent competition on the basis of quantitative food web structure (e.g. Müller et al , ; Lewis et al , ; van Veen et al , ; Hirao & Murakami, ; Alhmedi et al , ) have actually used experiments to verify the outcome in terms of realised dynamics (but see Morris et al , ; Tack et al , ). In the context of converting food web structure into concrete predictions on dynamics, the critical words of Robert Paine () still ring as urgently as they did when they were written 25 years ago: ‘I know of no one who, having assembled a data set on feeding relationships, considers those data to constitute much more than an incomplete preliminary description.’ Hence, a ‘focus on dynamic rather than static (= completely descriptive) properties [of food webs] would constitute a primary desideratum’ (Paine, , pp.…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with the study by Bianchi & Werf (2004) who found the availability of non-pest aphids in the non-crop habitats leads to conservation of ladybirds for enhanced biological control. Thrips, aphids and stink bugs damage was reported to be reduced as a result of increased insect natural enemies in different field margin vegetation (Eyre et al, 2011;Alhmedi et al, 2011 andPease &Zalom, 2010 respectively). Other insect pests like moth larvae (Balzan & Moonen, 2014) and olive psyllids (Paredes et al, 2013) were also found to be effectively managed through enhanced biological control attributed to the non-crop vegetation diversity.…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%